Genetic characteristics of the diploid offsprings in potato Cooperation 88 induced by diploid donor IVP101 - Wang, Rongyan; Feng, Yan; Peng, Jing; Tan, Chen; Zhou, Jian; Hai, Yang; Luo, Youwei; Hao, Dahai; Li, Canhui; Tang, Wei (Frontiers in Plant Science, 2024)
Diploid lines (2n = 2x = 24) derived from tetraploid potato cultivars have been utilized to hybridize with wild diploid potato species, yielding fertile offspring. Utilizing the pollen of S. tuberosum Group Phureja, such as IVP101, as an inducer for wide hybridization with tetraploid cultivars represents a common method for producing diploids. Possible mechanisms for diploid formation include the parthenogenesis of tetraploid cultivars (the resulting diploids are referred to as dihaploids), heterozygous diploids or the complete elimination of the inducer genome in the zygote. However, reports have indicated that the phenomenon of the inducer nuclear genome not being fully eliminated has been observed. The phenomenon of incomplete elimination of the inducer's cytoplasmic genome remains underreported in current literature. Occasional paternal inheritance has been observed at low frequencies (not exceeding 5%) in hybrid offspring of the genera Daucus, Medicago, and Pinus. In this study, we investigated the genetic composition of chloroplast and nuclear genomes in 43 diploid offspring generated from the cross between tetraploid potato cultivar Cooperation 88 (C88) and IVP101. We found that all diploid offspring share the same chloroplast genomic sequence as C88 and no evidence of paternal chloroplast inheritance was found. Used SNP data to calculate the theoretical introgression index of IVP101 with diploid offsprings. The results showed that the inducer’s nuclear genome was involved in the nuclear genome of the diploid offspring of purple stem, indicating that the inducer nuclear genome was not completely eliminated in the nuclear genome of the three diploid offsprings with purple stem. Furthermore, we conducted a comparative analysis of the chloroplast genomes of the Solanum genus. The results indicated that (1) the chloroplast genome sizes of the 14 Solanum species ranged from 154,289 bp to 155,614 bp, with a total number of genes ranging 128-141, and with ycf1 and rps19 pseudogenes appearing at the IRB/SSC and IRA/LSC boundaries, respectively; (2) eight divergent hotspots distributed in the LSC and SSC regions of the Solanum chloroplast genomes were identified; (3) positive selection was detected in the clpP, rbcL, rps15, and rps4 genes, likely contributing to the adaptation of Solanum species to different habitats.